Sanksi Hukum Penyelenggaraan Pesta Perkawinan Ditengah Pandemi Covid-19 Menurut Peraturan Gubernur Jawa Timur Nomor 53 Tahun 2020 Tentang Protokol Kesehatan Dalam Pencegahan Dan Pengendalian Corona Virus Disease 2019 - Samsul Huda; Sofiatur Rohmah (JUSTNESS - Jurnal Hukun dan Agama, 2021)
In the Covid-19 regulation, there are many community activities that are restricted by the government, postponed or even stopped. This pandemic situation also has implications for the implementation of marriages and has an impact on the wedding party support industry. In this Pandemic period, those who force themselves to hold wedding receptions are required to follow the rules that have been in effect and always heed the health protocols. If you do not comply and violate it, the event will be disbanded and will be subject to sanctions.To answer the above problems, the authors use normative or library research methods, namely reading and taking notes and processing research materials. So the author conducts research related to the subject matter with the source of legal material, and the research method used is normative legal research that departs from the existence of statutory regulations.The purpose of this study is to find out the forms of violations of the implementation of ceramics in the midst of the Covid-19 Pandemic, as well as the legal consequences of violating marriage parties during the Covid-19 pandemic.Marriage is a sacred thing for human life, not a few people, both young and old, want to immediately carry out a marriage or marriage contract and its reception, due to the number of community activities that are limited by the Government due to the Corona Disease 2019 virus, the implementation of wedding parties is also limited. Keyword: Offense, Marriage, Covid-19